Performance Analysis of Blended Tyre Pyrolysis Oil (TPO) Against Diesel in A YANMAR TF-120 Single Cylinder Diesel Engine - Lim, Jin Wei; Rishinddren, Mathialagan; Muhammad Izzat Nor, Ma'arof; Girma, Tadesse Chala (Roman Science Publications Inc., 2022)
This paper experimentally investigates the performance of blended tyre pyrolysis oil (50% diesel / 50% TPO) against pure diesel in a YANMAR TF-120 single cylinder diesel engine. The brake power and torque were measured to calculate the brake thermal efficiency and brake specific fuel consumption for the purpose of making a comparison. It was observed that the 50% diesel / 50% TPO fuel produced a lower torque of 20 Nm in contrast to diesel of 32 Nm. On the positive note, the TPO fuel shows a fewer fuel consumption compared to the diesel to produce the required energy to drive the engine speed. The calorific value of the TPO oil differs by 3% compared to the diesel fuel which does not much impact the performance of the engine. The TPO managed to produce the similar amount of brake power output in comparison to diesel while simultaneously being more fuel efficient. Conclusively, the use of the TPO as an alternative fuel for diesel is indeed promising. For the future, it is recommended that a different blend of TPO is tested against pure diesel.